A Comparative Study of Faculties Working on Tenure Track System and in Basic Pay Scales in Peshawar - Shakeel Ahmad, Shaukat Ali, (JELM, 2023)
The major intension of instant study was to evaluate performance of the teachers who were recruited under Basic Pay Scale (BPS) and those who were appointed on TTS. It is fresh project of the HEC with the objective to attract fresh talent. Therefore, the population of the study embraced entire teachers working in the universities of Khyber Pakhtunkhwa. Moreover, entire Assistant Professors either working under BPS or TTS was selected as sample of the study. Subsequently, a questionnaire comprising thirty items on likert five point scales (one for the Assistant Professor appointed under BPS and on TTS) was developed. Prior to administration, validation was conducted .T-test was applied on the collected data. The results of the study showed no difference between the performances of the teachers appointed under BPS and TTS. Nevertheless the Assistant Professors who were working on TTS were not satisfied with the safety and constancy of their job. Moreover, both faculty members have contemplated research and publication as cause of anxiety. Likewise, Assistant Professor working on BPS was reluctant to convert to TTS. Albeit, Assistant Professor working on TTS agreed that research motivate and improve the relevant subject knowledge. However, result of the study pinpointed that job security of TTS faculty must be corroborated and obligatory modifications should be incorporated in TTS statutes so as attract the faculty members who are presently working under BPS.